2015
DOI: 10.1088/0004-637x/800/1/15
|View full text |Cite
|
Sign up to set email alerts
|

The Degeneracy of M33 Mass Modeling and Its Physical Implications

Abstract: The Local Group galaxy M33 exhibits a regular spiral structure and is close enough to permit high resolution analysis of its kinematics, making it an ideal candidate for rotation curve studies of its inner regions. Previous studies have claimed the galaxy has a dark matter halo with an NFW profile, based on statistical comparisons with a small number of other profiles. We apply a Bayesian method from our previous paper to place the dark matter density profile in the context of a continuous, and more general, p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…The finding of a dependency of the inner shape of the DM halo on the mass-to-light ratio is in agreement with the analysis of Hague & Wilkinson (2015). These authors used a Bayesian approach to constrain the mass distribution of M33 from the kinematics of Corbelli & Salucci (2000).…”
Section: Comparison With Previous Worksupporting
confidence: 80%
See 2 more Smart Citations
“…The finding of a dependency of the inner shape of the DM halo on the mass-to-light ratio is in agreement with the analysis of Hague & Wilkinson (2015). These authors used a Bayesian approach to constrain the mass distribution of M33 from the kinematics of Corbelli & Salucci (2000).…”
Section: Comparison With Previous Worksupporting
confidence: 80%
“…They have also shown that the distribution of dark matter is consistent with a model for which the mass density steeply decreases in the centre of the halo (the cosmological cusp à la Navarro-Frenk-White, see Navarro et al 1997), and whose concentration agrees well with the halo mass-concentration relation from Λ Cold Dark Matter simulations (Ludlow et al 2014). Comparable results have been obtained by Hague & Wilkinson (2015), but from a lower resolution Hi curve derived earlier by Corbelli & Salucci (2000). They concluded that models with density profiles with an inner slope shallower than 0.9 (as measured at R ∼ 0.5 kpc, the first velocity point of their rotation curve) are only compatible with 3.6-µm mass-to-light ratios Υ > 2, while cuspier densities can coexist with Υ < 2.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…These criteria lead to an additional 5 galaxies. Finally we also included the rotation curve of M33 (taken from Corbelli et al 2014), which is a galaxy previously claimed to have a strongly cusped dark matter halo (Corbelli et al 2014;Hague & Wilkinson 2015). For this galaxy Corbelli et al (2014) have not reported the stellar surface brightness profile, but have immediately derived the surface density profile of the stars from a pixel by pixel population synthesis analysis.…”
Section: Sample Selectionmentioning
confidence: 99%
“…The parameters are motivated by previous observations and models of M33's rotation curve (e.g. Regan & Vogel 1994;Corbelli & Salucci 2000;Seigar 2011;Hague & Wilkinson 2015;Kam et al 2015). M33 is a fairly low-mass spiral galaxy close to the Milky Way.…”
Section: Galaxy Components and Density Profilesmentioning
confidence: 99%